2012
DOI: 10.1016/j.ajhg.2012.01.018
|View full text |Cite|
|
Sign up to set email alerts
|

Syndrome of Hepatic Cirrhosis, Dystonia, Polycythemia, and Hypermanganesemia Caused by Mutations in SLC30A10 , a Manganese Transporter in Man

Abstract: Environmental manganese (Mn) toxicity causes an extrapyramidal, parkinsonian-type movement disorder with characteristic magnetic resonance images of Mn accumulation in the basal ganglia. We have recently reported a suspected autosomal recessively inherited syndrome of hepatic cirrhosis, dystonia, polycythemia, and hypermanganesemia in cases without environmental Mn exposure. Whole-genome mapping of two consanguineous families identified SLC30A10 as the affected gene in this inherited type of hypermanganesemia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
368
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(379 citation statements)
references
References 55 publications
8
368
1
2
Order By: Relevance
“…Recent genetic studies identified mutations in the human gene that were associated with hypermanganesemia. Loading of this metal is observed in both tissues, resulting in cirrhosis of the liver and Parkinson-like motor impairments (94,95). Due to the roles of manganese (and zinc) in combating infection, one speculation is that this transporter may also participate in the host immune response.…”
Section: Roles Of Other Transportersmentioning
confidence: 99%
“…Recent genetic studies identified mutations in the human gene that were associated with hypermanganesemia. Loading of this metal is observed in both tissues, resulting in cirrhosis of the liver and Parkinson-like motor impairments (94,95). Due to the roles of manganese (and zinc) in combating infection, one speculation is that this transporter may also participate in the host immune response.…”
Section: Roles Of Other Transportersmentioning
confidence: 99%
“…Homozygous mutations of the ZnT10 gene cause Parkinsonism and dystonia with hypermanganesemia, polycythemia, and hepatic cirrhosis (OMIM 613280) (341,417). In these patients, not zinc, but systemic and cellular manganese homeostasis was disturbed (341,417), suggesting that the primary function of ZnT10 is manganese transport (see sect. IIIA).…”
Section: Znt10mentioning
confidence: 99%
“…Homozygous loss-of-function mutations of the ZnT10/ SLC30A10 gene cause Parkinsonism and dystonia with hypermanganesemia, which are ameliorated by metal chelation therapy (341,417).…”
Section: B Genetic Diseases Of Zinc Transporters and Therapeutic Appmentioning
confidence: 99%
“…For example, toxic effects of hypermanganesemia are seen in an inherited Mn overload syndrome associated with genetic defects in SLC30A10 (15,16). Recent studies have shown that SLC30A10 is a cell surfacelocalized Mn efflux transporter that reduces cellular Mn levels and protects against Mn toxicity (17,18).…”
mentioning
confidence: 99%